Personalised dissemination of legal information - Janecek, V (IOS Press, 2019)
A proper functioning of any legal system requires people to know the law. Our knowledge of the law, however, depends on how legal information are communicated. Currently, however legal information are communicated rather poorly. We are still missing opportunities that Big Data and algorithms offer in relation to how the law is published, disseminated, and accessed. This Chapter focuses on dissemination of legal information. It argues that we should strive for personalised dissemination. By highlighting and analysing examples from the history of legal publication, it argues that the shift to personalised dissemination of legal information does not pose a threat to the existing legal systems. Instead, it could enhance the overall efficiency and sustainability of our legal communication, increase our knowledge of the law, while reducing the total costs. The Chapter therefore makes a case for a new era in publication and communication of the law – the era of personalised dissemination of legal information.